PENDEKATAN FAKTOR MAKRO DAN FAKTOR MIKRO YANG DIPERTIMBANGKAN KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PERUMAHAN (Studi Pada Industri Perumahan di Banjarmasin) - Faisal Akly; Arief Budiman; Nuril Huda (JWM (JURNAL WAWASAN MANAJEMEN), 2020)
This study analyzes the approach of macro factors and micro factors that consumers consider on housing purchase decisions, research on this issue is how the influence of the macro approach and micro approaches to housing purchases. The research sample of 100 respondents. Data analysis uses multiple linear regression. The results showed that the macro factor approach and the micro factor approach had a significant effect on housing purchase considerations